EVALUASI KELAYAKAN TEKNIS, SOSIAL EKONOMI DAN LINGKUNGAN INSTALASI PENGOLAHAN LUMPUR TINJA (IPLT) DI KAWASAN STRATEGIS KABUPATEN SUBANG - Wulan Rachmawati; Rina Marina; Iskandar Muda Purwaamijaya (Kokoh, 2023)
Sanitation is a deliberate behavior in a clean living culture with the aim of preventing humans from coming into direct contact with dirt and hazardous waste materials and it is hoped that this effort will maintain and improve human health. There are many efforts that can be taken in the environmental sanitation business, especially the handling of domestic liquid waste, the Sludge Treatment Plant (IPLT) system can be applied. This study aims to evaluate the technical, socio-economic and environmental feasibility of the IPLT which is planned to be built in Jalupang Village, Kec. Kalijati, Kab. Subang. The purpose of this study is to determine whether the location of the plan is feasible to build IPLT, planning for IPLT processing units and RAB IPLT. The results of the analysis show that the location of the IPLT development plan is acceptable, the treatment unit can treat waste that is safe for disposal to the environment and requires a fee of RP. 7,923,104,000.Keywords:Â Feces, Infrastructure, Liquid Waste, Planning, SanitationÂ